The spread of Reynoutria species (Polygonaceae) in Kampinos National Park and its vicinity (Central Poland) (CHORNOMORSKI BOTANICAL JOURNAL, 2018)
Knotweed taxa: Reynoutria japonica, R. sachalinensis and R. ×bohemica have been classified as the most dangerous invasive plants in Europe, North America, and other regions with cool climates. In Poland they are included on the list of 16 alien plant species which, when introduced into the natural environment, pose a threat to native biodiversity or natural habitats. Despite the serious threat they pose, Reynoutria species are still grown as ornamental plants, and are sometimes planted in hedges. Studies aimed at the identification of the range and the method of spread of knotweeds in settlement areas in Kampinos National Park and its vicinity were carried out from 2012. In mid-2018 there were 176 known sites where different species of Reynoutria were found. Most of these sites (118) were formed by R. japonica. R. ×bohemica was found on 54 sites, and R. sachalinensis only on four sites. Home gardens are a source of Reynoutria species spread in the region of Kampinoska Forest (national park with its buffer zone). Our results showed that the most of the Reynoutria species sites were located within the administrative borders of investigated localities, at different distances from home gardens, where these plants are grown. Although the distribution of knotweeds is largely limited to ruderal habitats, these invasive plants, especially R. japonica and R. ×bohemica, create a threat to semi-natural and natural biocoenoses at Kampinos National Park. R. sachalinensis was found only in villages on the periphery of KNP. Giant knotweed usually occupies large areas and form dense, homogeneous populations. It is necessary to constantly monitor the existing sites of knotweeds and prevent the formation of new stands in the area of Kampinos National Park and its close vicinity.
Keywords: invasive plants, rural areas, synanthropic habitats, protected area.